2012
DOI: 10.6088/ijaser.0020101016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of Spirulina against Gamma irradiation induced oxidative stress and tissue injury in rats

Abstract: doi:10.6088/ijaser.0020101016 Abstract: Many antioxidants have been investigated as hepato-protectors against ionizing radiation induced injury since they reduce the oxidative effect of the reactive oxygen species on normal cells. Spirulina is a potent scavenger of a variety of free radicals. The aim of this study was to investigate the radio-protective effect of Spirulina algae against oxidative stress and tissue injury caused by gamma radiation. Rats were irradiated at two doses of 2 and 4Gy from cesium-137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Comparisons were made as follows: a group I vs groups II, III, IV, V; b group II vs group III, IV, V; c group III vs group IV, V; d group IV vs group V. The symbols represent statistical significance at *P < 0.05. Statistical analysis was calculated by one-way ANOVA followed by the Student Newman-Keul's test ionizing-radiation induced oxidative stress and organ injury (Rehab 2012). A study on Spirulina maxima has reported to show protection against hepatotoxic, hyperglycaemic and hyperlilidaemic activity, which was analyzed on fructose-induced diabetic rats (Jarouliya et al 2012).…”
Section: Effect Of Spirulina Fusiformis On Pancreas Liver and Kidneymentioning
confidence: 99%
“…Comparisons were made as follows: a group I vs groups II, III, IV, V; b group II vs group III, IV, V; c group III vs group IV, V; d group IV vs group V. The symbols represent statistical significance at *P < 0.05. Statistical analysis was calculated by one-way ANOVA followed by the Student Newman-Keul's test ionizing-radiation induced oxidative stress and organ injury (Rehab 2012). A study on Spirulina maxima has reported to show protection against hepatotoxic, hyperglycaemic and hyperlilidaemic activity, which was analyzed on fructose-induced diabetic rats (Jarouliya et al 2012).…”
Section: Effect Of Spirulina Fusiformis On Pancreas Liver and Kidneymentioning
confidence: 99%
“…Animals were placed in a specially designed well-ventilated acrylic container and the whole body of the animals were exposed to 5 Gy as a single shot dose, given at a dose rate of 0.84 Gy/min from the biological irradiator gamma cell-40, cesium-137 source (Atomic Energy Agency, Canada Limitd, AECL), belonging to National Center for Radiation Research and Technology (NCRRT), Cairo (Rehab and Ibrahim, 2012).…”
Section: Radiation Facilitymentioning
confidence: 99%